(untitled) (Universal International Scientific Journal, 2026)
This article interprets reading and mother tongue textbooks in primary education as important didactic tools for shaping students’ thinking. The system of texts, questions, and tasks in the textbooks is scientifically described as a step-by-step process that leads students from simple reading to deep comprehension, from comprehension to analysis, and from analysis to independent and critical thinking. Exercises such as picture-based storytelling, creating sentences and proverbs from given words, and analyzing problem situations are evaluated as mechanisms for enhancing cognitive activity. Based on the experience of integrated textbooks, effective methodological approaches for developing independent thinking are proposed.